Dis-moi quels médias tu préfères, je te dirai comment tu votes - Michaël Pino; Pascal Marchand (Communication)
Field research, inscribed in a controversy about the impact on receivers of various types of political programs in the media (the written press and television) in presented. Here, we propose to privilege the real and complex choices of individuals in this political offer. A statistical typology of media practices is proposed and then put into relation with the behaviours, attitudes, and political representations. We show that subjects who have weak media practices or who limit their consumption to entertainment programs have a lower cultural and political behaviour level than those who follow journalistic programs or who read engaged written press.